Pengaruh Kompetensi Dan Beban Kerja Terhadap Perilaku Perawat Dalam Menerapkanasuhan Keperawatan Profesional Di Instalasi Rawat Inap RSUD Praya - HMENAP, Menap Menap; Achmalona, Teguh (Jurnal Kesehatan Qamarul Huda, 2019)
Nursing services are an integral part of health services which have a very strategic position in an effort to improve the quality of services in hospitals. With this condition a nurse is required to have the ability and professionalism in implementing professional nursing care in a hospital service. The purpose of this study was to determine the effect of competency factors, and workload on nurses' behavior in implementing professional nursing care in the Praya Hospital inpatient installation. The research design used was quantitative analytic with cross sectional approach. The sampling technique uses cluster random sampling with a sample of 114 respondents. Data were collected using a questionnaire and observation sheet, then analyzed using the ordinal regression test. The results of the statistical test by stimulatory results obtained p value of 0,000 <? = 0.05, meaning that all independent variables together affect the dependent variable. While partial statistical test results for each variable obtained results, namely competency (p <0.008) and workload (p <0.012). Multivariate analysis showed competence was the most dominant variable influencing the behavior of nurses in applying professional nursing care with a value (p <0.008). The behavior of nurses in implementing professional nursing care in hospitals is influenced by several factors including competency and workload. These aspects certainly need to be considered and managed well in the hope of getting better nurse performance results for the creation of maximum nursing services.